2019
DOI: 10.1371/journal.pone.0220136
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation and learning in medical consultations about congenital heart defects

Abstract: In this article, patient activity in 8 audio recorded specialist consultations on fetal cardiology is investigated in order to explore how, why and when patients tend to participate in encounters in which the doctor dominates the interaction. The overall question is: How can the participation of patients in the consultations be connected to the development of higher levels of health literacy, i.e. to interactive literacy and to critical literacy? Patient participation is here understood as interactive action a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…While prior studies have assessed parental perceptions and clinician-reported practices when counseling about a prenatal CHD diagnosis [ 1 , 34 , 42 ], this study is one of the first, to our knowledge, to examine the language used in fetal cardiology consultations by analyzing audio-recordings of those encounters [ 43 ]. As clinician discourse styles may vary based on prior experiences, training, geographical region, and sociocultural factors, the generalizability of our study findings may be limited as the data analyzed was from one academic institution and limited to five fetal cardiology clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have assessed parental perceptions and clinician-reported practices when counseling about a prenatal CHD diagnosis [ 1 , 34 , 42 ], this study is one of the first, to our knowledge, to examine the language used in fetal cardiology consultations by analyzing audio-recordings of those encounters [ 43 ]. As clinician discourse styles may vary based on prior experiences, training, geographical region, and sociocultural factors, the generalizability of our study findings may be limited as the data analyzed was from one academic institution and limited to five fetal cardiology clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Helsekommunikasjon handler altså om måter å kommunisere på som kan arte seg ulikt for ulike kulturer. Det kan ofte vise seg at det kan vaere betydelig avstand mellom det helsepersonell antar at pasienter forstår og det pasientene faktisk forstår (Bellander & Karlsson, 2019;Jenum & Pettersen, 2014). Horntvedt (2015) sier at enhver kultur har tause regler og normer som former og styrer våre handlinger og måter å kommunisere på, noe som kan føre til usikkerhet og misforståelse for andre.…”
Section: Flerkulturell Helsekommunikasjonunclassified